In Vivo Head‐To‐Head Comparison of [18F]GTP1 and [18F]PI2620 in Alzheimer's Disease. (20th December 2022) - Bohorquez, Sandra Sanabria; Constantinescu, Cristian; Manser, Paul T; Gunn, Roger N; Russell, David S; Tonietto, Matteo; Bullich, Santiago; Stephens, Andrew W; Mueller, Andre; Klein, Gregory; Teng, Edmond; Pickthorn, Karen
Abstract: Background: Several radiotracers targeting tau pathology in Alzheimer's disease (AD) are being used in human studies. Although abundant imaging characterization data exist for individual tracers there are only sparse in vivo data directly comparing tracers in head‐to‐head studies. As the use of tau PET increases, it is of paramount importance to enable multi‐tracer, multi‐center, multi‐national observational and therapeutic trials. We present the direct in vivo comparison of [ 18 F]GTP1 and [ 18 F]PI2620. Methods: To date, 21 subjects (70±6 years; 12F) have completed imaging with both [ 18 F]GTP1 and [ 18 F]PI2620: 10 prodromal, 9 mild, one moderate AD subjects (Aβ+), and one Aβ‐ cognitively unimpaired subject. Thirty minutes images were acquired 60 and 45 min after [ 18 F]GTP1 and [ 18 F]PI2620 administration, respectively. SUVR was calculated using the inferior cerebellum and used to compare tau‐specific binding and off‐target signal characteristics between the two tracers. The choroid plexus was defined manually for each subject. The whole cortical gray (WCG) and cerebellum rims were defined using the gray and white‐matter SPM tissue segmentation images (Figure 1). Results: Tracer distribution was similar for both tracers (Figures 2 and 3). Hammer atlas cortical SUVRs were linearly correlated (r 2 =0.88). Higher cortical [ 18 F]PI2620 SUVR were observed in some subjects and regions (Figure 3). A lower SUVR correlation was observed in subcortical regions (r 2 =0.57). Regional comparisons are shown in Figure 4. Conclusions: The tau pathology distribution was similar for both tracers although each tracer presents a distinct off‐target signal pattern. These preliminary results support the development of categorical and standardized quantification scales for using both tracers in future studies and bridging existing data sets. Figure 1. Delineation of cortex and cerebellum rims. The combined gray and white matter SPM segmentations were binarized and the ventricles and internal CSF spaces filled to create a mask. Figure 2. [18F]GTP1 and [18F]PI2620 SUVR images. Figure 3. [18F]GTP1 and [18F]PI2620 SUVR in WCG and in vivo Braak regions. Figure 4: [18F]GTP1 and [18F]PI2620 SUVR correlation in target cortical regions, and off‐target signal in choroid plexus (CP), WCG and cerebellum (CBL) rims, and subcortical structures (CAU: caudate; PUT: putamen; PAL: pallidum; THA: thalamus; NAc: nucleus accumbens; SN: substantia nigra) and centrum semiovale (WM).